Soft magnetic powder, dust core, magnetic element, and electronic apparatus

A stabilized soft magnetic powder composition with controlled amorphous and crystal phases addresses oxidation and density issues, enhancing permeability and reducing magnetic loss for high-frequency applications.

JP2025014680APending Publication Date: 2025-01-30SEIKO EPSON CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023117441
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-19
Publication Date
2025-01-30

AI Technical Summary

Technical Problem

The existing soft magnetic powder compositions are prone to oxidation, have insufficient density, and do not adequately reduce hysteresis loss, making them unsuitable for high-frequency applications in magnetic elements.

Method used

A specific composition of soft magnetic powder with controlled amorphous and crystal phases, stabilized by chromium distribution, enhances oxidation resistance and density, while optimizing permeability and reducing magnetic loss.

Benefits of technology

The new composition achieves high permeability and density in magnetic elements, facilitating miniaturization and reducing manufacturing complexity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025014680000001_ABST
    Figure 2025014680000001_ABST
Patent Text Reader

Abstract

To provide soft magnetic powder that can be used to manufacture a green compact with high density and magnetic permeability, has a reduced coercive force, and can be easily manufactured, a dust core including the soft magnetic powder, a magnetic element comprising the dust core, and an electronic apparatus comprising the magnetic element.SOLUTION: Soft magnetic powder has a composition represented by FexCuaNbb(Si1-y(B1-zCrz)y)100-x-a-b [a, b, x, y, and z satisfy 0.3≤a≤2.0, 2.0≤b≤4.0, 75.5≤x≤79.5, 0.55≤y≤0.91, and 0.015≤z≤0.185], has an amorphous phase and a crystalline phase, and when the Cr content determined by an OES is defined as X(Cr), and the Cr content and the B content in the amorphous phase determined by an EDX as Y(Cr) and Y(B), satisfies the formula (1) and the formula (2). (1) X(Cr)<Y(Cr)≤X(Cr)+1.0. (2) 3.0≤Y(B)≤15.0.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a soft magnetic powder, a dust core, a magnetic element, and an electronic device. [Background technology]

[0002] In various mobile devices equipped with magnetic elements containing powder magnetic cores, in order to reduce size and increase output, the switching power supply must be compatible with high frequencies and high currents in conversion frequency, which requires that the soft magnetic powder contained in the powder magnetic cores must also be compatible with high frequencies and high currents.

[0003] In Patent Document 1, Fe x Cu a Nb b (Si 1-y B y ) 100-x-a-b [where a, b, and x are each in atomic percent and are numbers that satisfy 0.3≦a≦2.0, 2.0≦b≦4.0, and 73.0≦x≦79.5. Also, y is a number that satisfies f(x)≦y<0.99. Note that f(x)=(4×10 -34 )x 17.56 The present invention discloses a soft magnetic powder having a composition represented by the formula: and containing 30% by volume or more of a crystal structure having a grain size of 1.0 nm to 30.0 nm. Such a soft magnetic powder has high magnetic permeability and can realize a magnetic element that is miniaturized. In addition, since such a soft magnetic powder contains minute crystals, it can achieve low iron loss in the high frequency range. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2019-189928 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, the soft magnetic powder described in Patent Document 1 has a problem that it is easily oxidized depending on the composition, and the density during molding cannot be sufficiently increased. The density of the compact affects the magnetic permeability of a magnetic element having a powder magnetic core. Therefore, the realization of a soft magnetic powder that has excellent oxidation resistance and can be used to produce a compact with high density and magnetic permeability is an issue.

[0006] In order to reduce iron loss in the high frequency range, it is important to reduce the coercive force, which causes hysteresis loss. However, the soft magnetic powder described in Patent Document 1 does not have a sufficiently low coercive force.

[0007] Furthermore, the soft magnetic powder described in Patent Document 1 also discloses that an amorphous structure and a fine crystalline structure are mixed. In order to realize such a configuration, it is necessary to manufacture a powder dominated by an amorphous structure, and then heat-treat the powder to partially crystallize it. However, the coercive force after heat treatment of the soft magnetic powder described in Patent Document 1 is likely to vary depending on the heat treatment conditions. For this reason, it is also an issue to efficiently manufacture a soft magnetic powder with a low coercive force.

[0008] Therefore, the challenge is to realize a soft magnetic powder that can be easily manufactured and has low coercive force, and that can produce a green compact with high density and magnetic permeability. [Means for solving the problem]

[0009] The soft magnetic powder according to the application example of the present invention is The composition determined by the solid-state optical emission spectrometer (OES) is the composition formula Fe x Cu a Nb b (Si 1-y (B 1-z Cr z ) y ) 100-x-a-b [a, b, x, y, z are 0.3≦a≦2.0, 2.0≦b≦4.0, 75.5≦x≦79.5, 0.55≦y≦0.91, 0.015≦z≦0.185, .] It is expressed as The amorphous phase is composed of an amorphous structure in which Fe is the constituent element with the highest concentration, and the crystalline phase is composed of a crystalline structure in which Fe is the constituent element with the highest concentration, When the Cr content [atomic %] determined by OES is designated as X(Cr), and the Cr content [atomic %] and B content [atomic %] of the amorphous phase determined by an energy dispersive X-ray fluorescence analyzer (EDX) are designated as Y(Cr) and Y(B), respectively, the following formulae (1) and (2) are satisfied. X(Cr) <Y(Cr)≦X(Cr)+1.0 (1) 3.0≦Y(B)≦15.0 (2)

[0010] The powder magnetic core according to the application example of the present invention is The soft magnetic powder according to the application example of the present invention is included.

[0011] The magnetic element according to the application example of the present invention includes: The present invention is provided with a powder magnetic core according to an application example of the present invention.

[0012] The electronic device according to the application example of the present invention includes: The magnetic element according to the application example of the present invention is provided. [Brief description of the drawings]

[0013] [Figure 1] FIG. 2 is a schematic diagram of an observation image obtained by enlarging and observing a cross section of a particle of the soft magnetic powder according to the embodiment. [Diagram 2] FIG. 2 is a plan view illustrating a schematic diagram of a toroidal type coil component. [Diagram 3] FIG. 2 is a see-through perspective view that typically illustrates a closed magnetic circuit type coil component. [Figure 4] FIG. 1 is a perspective view showing a configuration of a mobile personal computer, which is an electronic device including a magnetic element according to an embodiment. [Diagram 5]FIG. 1 is a plan view showing a configuration of a smartphone, which is an electronic device including a magnetic element according to an embodiment. [Figure 6] 1 is a perspective view showing a configuration of a digital still camera, which is an electronic device including a magnetic element according to an embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The soft magnetic powder, the dust core, the magnetic element, and the electronic device of the present invention will be described in detail below with reference to preferred embodiments shown in the accompanying drawings.

[0015] 1. Soft magnetic powder The soft magnetic powder according to the embodiment is a powder exhibiting soft magnetism. Such soft magnetic powder can be used for any purpose, but for example, the particles are bound together via a binder and used to manufacture various types of compacts such as dust cores and electromagnetic wave absorbing materials.

[0016] 1.1. Overview of soft magnetic powder The soft magnetic powder according to the embodiment has a composition determined by an optical emission spectrometer (OES) of the composition formula Fe x Cu a Nb b (Si 1-y (B 1-z Cr z ) y ) 100-x-a-b [a, b, x, y, z are 0.3≦a≦2.0, 2.0≦b≦4.0, 75.5≦x≦79.5, 0.55≦y≦0.91, 0.015≦z≦0.185, .] It is expressed as:

[0017] The solid-state optical emission spectrometer is a device that performs pretreatment on soft magnetic powder, performs chemical analysis on the solution sample, and quantifies the concentration of each element. Therefore, the composition obtained by OES can be said to be the composition of the entire soft magnetic powder.

[0018] Examples of the pretreatment mentioned above include the pretreatments specified in JIS G 1258-0:2017, JIS G 1258-1:2014, JIS G 1258-2:2014, JIS G 1258-3:2014, JIS G 1258-4:2007, JIS G 1258-5:2007, JIS G 1258-6:2007, JIS G 1258-7:2007, JIS G 1258-8:2017, etc.

[0019] Fig. 1 is a schematic diagram of an observation image obtained by enlarging and observing the cross section of a particle 1 of a soft magnetic powder according to an embodiment. That is, Fig. 1 is a partially enlarged view of the cross section of one particle 1.

[0020] Particle 1 shown in Fig. 1 has an amorphous phase 2 composed of an amorphous structure and a crystalline phase 3 composed of a crystalline structure. In particle 1, as shown in Fig. 1, for example, the amorphous phase 2 is a matrix, and granular crystalline phase 3 is dispersed in the matrix.

[0021] The amorphous phase 2 is composed of an amorphous structure having Fe as the highest concentration of the constituent element. The crystalline phase 3 is composed of a crystalline structure having Fe as the highest concentration of the constituent element. The particle 1 may contain other phases in addition to the amorphous phase 2 and the crystalline phase 3. Examples of other phases include the Cu segregation phase 6 shown in FIG. 1, which is composed of a crystalline structure having Cu as the highest concentration of the constituent element.

[0022] Here, the Cr content [atomic %] obtained by OES is designated as X(Cr), and the Cr content [atomic %] and B content [atomic %] of the amorphous phase 2 obtained by an energy dispersive X-ray fluorescence analyzer (EDX) are designated as Y(Cr) and Y(b). In this case, the soft magnetic powder according to the embodiment satisfies the following formulas (1) and (2).

[0023] X(Cr) <Y(Cr)≦X(Cr)+1.0 (1) 3.0≦Y(B)≦15.0 (2)

[0024] In such soft magnetic powder, Cr is added to the conventional five elements Fe, Cu, Nb, Si, and B, and the amount of Cr added is optimized. Cr is unevenly distributed in the amorphous phase 2. Specifically, as represented by the above formula (1), the Cr content in the amorphous phase 2 determined by EDX is higher than the Cr content in the entire powder determined by OES. The amorphous phase 2 contains B at a predetermined content. Specifically, as represented by the above formula (2), the B content in the amorphous phase 2 determined by EDX falls within a predetermined range.

[0025] According to the above-mentioned configuration, the oxidation resistance of the soft magnetic powder can be improved. As a result, when the soft magnetic powder is compressed, the density of the compact can be prevented from being reduced by oxides. As a result, the magnetic permeability of the compact can be increased.

[0026] In addition, in the soft magnetic powder according to the embodiment, the amorphous phase 2 in which Cr is unevenly distributed is stabilized, and the coarsening of the crystalline phase 3 is suppressed. Therefore, the soft magnetic powder according to the embodiment can have a low coercive force. The stabilization of the amorphous phase 2 means that the amorphous phase 2 is easily maintained in an amorphous state.

[0027] Furthermore, in order to mix the amorphous phase 2 and the crystalline phase 3, it is necessary to perform a heat treatment (crystallization treatment) after manufacturing the powder occupied by the amorphous phase 2 to partially crystallize it. In this case, the grain size (crystallite size) of the crystalline phase 3 is likely to change depending on the conditions of the crystallization treatment, and there is a risk of a coarse crystalline phase 3 being generated. The coarse crystalline phase 3 leads to an increase in coercive force. In contrast, in the soft magnetic powder according to the embodiment, Cr is added at a predetermined concentration, so that the amorphous phase 2 can be easily stabilized. As a result, regardless of the conditions of the crystallization treatment, it is easy to suppress the coarsening of the crystalline phase 3. In other words, according to the above configuration, a low coercive force can be easily realized without performing an operation such as significantly increasing the heating rate for the purpose of preventing excessive crystallization. Therefore, it can be said that the soft magnetic powder according to the present embodiment is easy to manufacture.

[0028] Moreover, in the soft magnetic powder according to the embodiment, the crystallite size measured by X-ray diffraction is preferably 20.0 nm or less, which allows the soft magnetic powder to have a sufficiently low coercive force.

[0029] The soft magnetic powder according to the embodiment will be described in detail below. 1.2.Composition As described above, the soft magnetic powder according to the embodiment has a composition determined by OES and expressed by the composition formula containing Fe, Cu, Nb, Si and B described above.

[0030] Fe (iron) has a significant effect on the basic magnetic properties and mechanical properties of the soft magnetic powder according to the embodiment.

[0031] The Fe content x is 75.5 atomic % or more and 79.5 atomic % or less, preferably 76.0 atomic % or more and 78.5 atomic % or less, more preferably 76.5 atomic % or more and 78.0 atomic % or less. If the Fe content x is below the lower limit, the saturation magnetic flux density of the soft magnetic powder decreases. On the other hand, if the Fe content x is above the upper limit, an amorphous structure cannot be stably formed during the production of the soft magnetic powder, so that the crystallite size becomes excessively large, leading to an increase in coercive force.

[0032] When the soft magnetic powder according to the embodiment is manufactured from raw materials, Cu (copper) tends to separate from Fe. Therefore, the inclusion of Cu causes fluctuations in the composition, and regions that are easily crystallized are partially generated in the particle 1. As a result, the precipitation of the Fe phase of a body-centered cubic lattice, which is relatively easy to crystallize, is promoted, and the crystalline phase having the above-mentioned crystallite size is easily formed.

[0033] The Cu content a is 0.3 atomic % or more and 2.0 atomic % or less, preferably 0.5 atomic % or more and 1.5 atomic % or less, more preferably 0.7 atomic % or more and 1.3 atomic % or less. If the Cu content a is below the lower limit, the crystal phase is not refined. On the other hand, if the Cu content a is above the upper limit, the mechanical properties of the soft magnetic powder may be reduced and the powder may become brittle.

[0034] When the alloy is subjected to heat treatment from a state where the alloy is occupied by an amorphous structure, Nb (niobium) contributes to refining the crystal phase 3 together with Cu. Therefore, the crystal phase 3 having the above-mentioned crystallite size is easily formed.

[0035] The Nb content b is 2.0 atomic % or more and 4.0 atomic % or less, preferably 2.5 atomic % or more and 3.5 atomic % or less, and more preferably 2.7 atomic % or more and 3.3 atomic % or less. If the Nb content b is below the lower limit, the refinement of the crystal phase 3 is impaired. On the other hand, if the Nb content b is above the upper limit, the mechanical properties of the soft magnetic powder may be reduced and the soft magnetic powder may become brittle. In addition, the magnetic permeability of the soft magnetic powder is reduced.

[0036] Si (silicon) promotes amorphization when the soft magnetic powder according to the embodiment is manufactured from raw materials. Therefore, when manufacturing the soft magnetic powder according to the embodiment, a homogeneous amorphous structure is first formed, and then, by crystallizing it, it becomes easier to form a crystal phase 3 with a more uniform crystallite diameter. The uniform crystallite diameter contributes to averaging the magnetocrystalline anisotropy in each crystal phase 3, so that the coercive force can be reduced and the magnetic permeability can be increased, contributing to improving the soft magnetic property.

[0037] B (boron) promotes amorphization when the soft magnetic powder according to the embodiment is manufactured from raw materials. Therefore, when manufacturing the soft magnetic powder according to the embodiment, a homogeneous amorphous structure is first formed, and then, by crystallizing it, a crystalline phase 3 with a more uniform crystallite size is easily formed. As a result, the coercive force can be reduced and the magnetic permeability can be increased, thereby improving the soft magnetism. In addition, by using Si and B in combination, amorphization can be promoted synergistically based on the difference in atomic radius between the two.

[0038] Cr (chromium) is unevenly distributed in the amorphous phase 2, thereby contributing to the stabilization of the amorphous phase 2. The stabilization of the amorphous phase 2 suppresses the coarsening of the crystalline phase 3 and also makes the crystallite diameter uniform. This allows the soft magnetic powder to have a low coercive force. In addition, Cr enhances the oxidation resistance of the soft magnetic powder. This makes it possible to suppress the density of the green compact from decreasing due to oxides when the soft magnetic powder is compressed. As a result, the magnetic permeability and saturation magnetic flux density measured in the green compact state can be increased.

[0039] Here, the total content of Si, B and Cr (Si+B+Cr) is set to 1, and the ratio of the total content of B and Cr (B+Cr) to this total content (Si+B+Cr) is set to y.

[0040] The y satisfies 0.55≦y≦0.91, preferably 0.60≦y≦0.90, and more preferably 0.65≦y≦0.80. This allows the amounts of Si, B, and Cr to be balanced. As a result, the soft magnetic powder can have a low coercive force and both the oxidation resistance and magnetic permeability can be improved in a well-balanced manner.

[0041] If y is below the lower limit, the amorphous phase 2 becomes unstable, making it difficult to reduce the coercive force. In addition, the oxidation resistance decreases, and the crystallite size becomes too small, decreasing the magnetic permeability. On the other hand, if y is above the upper limit, the Si concentration decreases, making it difficult to form the amorphous phase 2.

[0042] Moreover, the ratio of the Cr content to the total content (B+Cr) is represented by z. This z satisfies 0.015≦z≦0.185, preferably 0.030≦z≦0.150, and more preferably 0.045≦z≦0.120. This allows the amounts of B and Cr to be balanced. As a result, the soft magnetic powder can have a low coercive force while improving both the oxidation resistance and the magnetic permeability in a well-balanced manner.

[0043] If z is below the lower limit, it becomes difficult to reduce the coercive force. In addition, the oxidation resistance decreases, and the crystallite size becomes too small, decreasing the magnetic permeability. On the other hand, if z is above the upper limit, the B concentration decreases, making it difficult to form the amorphous phase 2.

[0044] The Si content is preferably 1.5 atomic % or more and 14.0 atomic % or less, more preferably 3.0 atomic % or more and 10.0 atomic % or less, and further preferably 4.0 atomic % or more and 8.0 atomic % or less, which can increase the magnetic permeability of the soft magnetic powder and reduce the coercive force.

[0045] The content of B is preferably 5.0 atomic % or more and 17.0 atomic % or less, more preferably 7.0 atomic % or more and 16.0 atomic % or less, and even more preferably 9.0 atomic % or more and 13.5 atomic % or less, which can increase the magnetic permeability of the soft magnetic powder and reduce the coercive force.

[0046] The Cr content is preferably 0.3 atomic % or more and 2.7 atomic % or less, more preferably 0.5 atomic % or more and 2.2 atomic % or less, and even more preferably 0.8 atomic % or more and 1.8 atomic % or less. This can further increase the oxidation resistance of the soft magnetic powder and further suppress the generation of oxides. As a result, the decrease in density of the compact due to oxides can be suppressed, and the magnetic permeability and saturation magnetic flux density of the compact can be further increased. In addition, the crystallite size of the crystalline phase 3 can be appropriately controlled, and the balance between low coercivity and high magnetic permeability can be further optimized.

[0047] The soft magnetic powder according to the embodiment has the above composition formula Fe x Cu a Nb b (Si 1-y (B 1-z Cr z ) y ) 100-x-a-b In addition to the composition represented by the formula, impurities may be contained. Examples of impurities include any elements other than those mentioned above, but it is preferable that the total content of impurities is 0.50 atomic % or less. Within this range, even if impurities are mixed in, the above effects are unlikely to be hindered, so the inclusion of elements that are either intentionally added or unavoidably mixed in is permitted.

[0048] The content of each element contained in the impurities is preferably 0.05 atomic % or less. Within this range, the impurities are not likely to impair the above-mentioned effects, and therefore their inclusion is permitted.

[0049] Among the impurities, the oxygen content is preferably 1500 ppm or less, and more preferably 800 ppm or less. If the oxygen content is within the above range, the generation of oxides that cause a decrease in the density of the green compact can be particularly suppressed.

[0050] The soft magnetic powder according to the embodiment has been described above, and the composition and impurities are determined by a solid-state optical emission spectrometer (OES). Examples of the solid-state optical emission spectrometer include SPECTRO LAB M9 manufactured by SPECTRO and QSN750 manufactured by OBLF.

[0051] Impurities may be detected by the following analytical methods, if necessary: ​​iron and steel-atomic absorption spectrometry as specified in JIS G 1257:2000, iron and steel-ICP atomic emission spectrometry as specified in JIS G 1258:2007, iron and steel-spark discharge atomic emission spectrometry as specified in JIS G 1253:2002, iron and steel-X-ray fluorescence spectrometry as specified in JIS G 1256:1997, and gravimetry, titration, and absorptiometry as specified in JIS G 1211 to G 1237.

[0052] In particular, when identifying C (carbon) and S (sulfur), the oxygen flow combustion (high-frequency induction heating furnace combustion)-infrared absorption method specified in JIS G 1211:2011 is also used. Specifically, the LECO carbon / sulfur analyzer, CS-200, can be used.

[0053] In particular, when specifying N (nitrogen) and O (oxygen), the nitrogen determination method for iron and steel specified in JIS G 1228:1997 and the general rules for oxygen determination method for metallic materials specified in JIS Z 2613:2006 are also used. Specific examples include LECO oxygen / nitrogen analyzers, TC-300 / EF-300, and LECO oxygen / nitrogen / hydrogen analyzer, ONH836.

[0054] 1.3. Amorphous phase The amorphous phase 2 is composed of an amorphous structure in which Fe is the most highly concentrated constituent element. The amorphous phase 2 and the crystalline phase 3 can be distinguished according to the presence or absence of uneven distribution of B. When elemental mapping analysis is performed on the cross section of the particle 1 using EDX, it is possible to distinguish between an area where B is unevenly distributed and an area where the concentration of B is lower than that of the uneven distribution. The former area can be regarded as the amorphous phase 2, and the latter area can be regarded as the crystalline phase 3. Incidentally, uneven distribution refers to a state in which the B concentration is higher than the surroundings. For example, in the B concentration distribution obtained by elemental mapping analysis, the area with high B concentration is displayed by color concentration or the like.

[0055] As described above, Cr is unevenly distributed in the amorphous phase 2. Therefore, as described above, Cr stabilizes the amorphous phase 2 by being unevenly distributed, and suppresses the coarsening of the crystal phase 3. In addition, it is considered that Cr, by being unevenly distributed in the amorphous phase 2, produces a pinning effect that suppresses the growth of crystals, and it is considered that this pinning effect can also suppress the coarsening of the crystal phase 3.

[0056] By performing elemental analysis by EDX on the cross section of particle 1, the concentrations of each element in amorphous phase 2 and crystalline phase 3 can be obtained. The Cr content Y (Cr) [atomic %] of amorphous phase 2 obtained by EDX satisfies the relationship represented by the following formula (1) with respect to the Cr content X (Cr) [atomic %] obtained by OES. X(Cr) <Y(Cr)≦X(Cr)+1.0 (1)

[0057] When the Cr content Y(Cr) of the amorphous phase 2 is below the lower limit, it can be said that Cr is not sufficiently distributed unevenly in the amorphous phase 2. In this case, the amorphous phase 2 cannot be sufficiently stabilized, and the coarsening of the crystal phase 3 cannot be sufficiently suppressed. On the other hand, when the Cr content Y(Cr) of the amorphous phase 2 exceeds the upper limit, Cr is excessively distributed unevenly in the amorphous phase 2, and the amorphous structure becomes unstable.

[0058] The lower limit of the formula (1) is preferably X(Cr)+0.1 or more, more preferably X(Cr)+0.2 or more, and even more preferably 1.5 or more. The upper limit of the formula (1) is preferably X(Cr)+0.8 or less, more preferably X(Cr)+0.6 or less, and even more preferably 2.5 or less.

[0059] The Cr content Y(Cr) of the amorphous phase 2 is defined as the average value of the Cr contents measured at five or more points in the amorphous phase 2 contained in the cross section of one particle 1.

[0060] Moreover, the concentration of B is optimized in the amorphous phase 2. This allows the crystallization temperature to be increased, making it easier to form the amorphous phase 2. In other words, B, whose concentration is optimized, contributes to the stabilization of the amorphous phase 2.

[0061] The B content Y (B) [atomic %] of the amorphous phase 2 determined by EDX satisfies the relationship represented by the following formula (2). 3.0≦Y(B)≦15.0 (2)

[0062] When the B content Y(B) of the amorphous phase 2 is below the lower limit, it can be said that B is not sufficiently present in the amorphous phase 2. In this case, the amorphous phase 2 cannot be sufficiently stabilized, and the coarsening of the crystalline phase 3 cannot be sufficiently suppressed. On the other hand, when the B content Y(B) of the amorphous phase 2 exceeds the upper limit, B is excessively present in the amorphous phase 2, and the amorphous structure becomes unstable.

[0063] The lower limit of the above formula (2) is preferably 4.0 or more, and more preferably 4.5 or more, while the upper limit of the above formula (2) is preferably 10.0 or less, and more preferably 7.0 or less.

[0064] The B content Y(B) of the amorphous phase 2 is defined as the average value of the B contents measured at five or more points in the amorphous phase 2 contained in the cross section of one particle 1.

[0065] The Fe content in the amorphous phase 2 is preferably 50.0 atomic % or more, more preferably 70.0 atomic % or more and 95.0 atomic % or less, and even more preferably 80.0 atomic % or more and 90.0 atomic % or less.

[0066] Furthermore, the Si content in the amorphous phase 2 is preferably 2.0 atomic % or more and 8.0 atomic % or less, more preferably 3.0 atomic % or more and 7.0 atomic % or less, and even more preferably 4.0 atomic % or more and 6.0 atomic % or less.

[0067] 1.4.Crystalline phase The crystal phase 3 is composed of a crystal structure in which Fe is the most concentrated constituent element. As represented by the following formula (3), it is preferable that the Cr content Z(Cr) [atomic %] of the crystal phase 3 determined by EDX satisfies the relationship represented by the following formula (3) with respect to the Cr content X(Cr) determined by OES. Z(Cr) <X(Cr) (3)

[0068] The Cr content in the crystalline phase 3 tends to decrease by the amount of Cr unevenly distributed in the amorphous phase 2. Therefore, by satisfying the above formula (3), the amorphous phase 2 can be further stabilized. If the Cr content Z(Cr) of the crystalline phase 3 exceeds the upper limit, the crystalline phase 3 may not be composed of a stable crystal structure. In this case, it may be difficult to sufficiently increase the magnetic permeability of the soft magnetic powder.

[0069] The lower limit of the above formula (3) does not have to be particularly set, but is preferably 0.3 or more, more preferably 0.5 or more, and even more preferably 0.8 or more. On the other hand, the upper limit of the above formula (3) is preferably X(Cr)-0.1 or less, more preferably X(Cr)-0.2 or less, and even more preferably 2.0 or less.

[0070] The Cr content Z(Cr) of the crystal phase 3 is defined as the average value of the Cr contents measured at five or more points in the crystal phase 3 contained in the cross section of one particle 1.

[0071] The Fe content in the crystal phase 3 is preferably 50.0 atomic % or more, more preferably 70.0 atomic % or more and 95.0 atomic % or less, and even more preferably 80.0 atomic % or more and 90.0 atomic % or less.

[0072] Furthermore, the Si content in the crystal phase 3 is preferably 3 atomic % or more and 9 atomic % or less, more preferably 4 atomic % or more and 8 atomic % or less, and even more preferably 5 atomic % or more and 7 atomic % or less.

[0073] The amorphous phase 2 and the crystalline phase 3 have been described above, and the above contents are determined by an energy dispersive X-ray fluorescence analyzer (EDX). An example of an energy dispersive X-ray fluorescence analyzer is NSS7 manufactured by Thermo Fisher Scientific. The accelerating voltage during analysis is 120 kV, and Cliff-Lorimer (MBTS) that does not take absorption correction into account is used for the quantification method using the EDX spectrum.

[0074] 1.5.Crystallite size The soft magnetic powder according to the embodiment preferably has a crystallite diameter of 20.0 nm or less, more preferably 3.0 nm or more and 15.0 nm or less, and even more preferably 6.0 nm or more and 13.0 nm or less, as measured by an X-ray diffraction method. If the crystallite diameter is within such a range, the crystallite diameter of the soft magnetic powder is optimized, so that the magnetic permeability of the soft magnetic powder can be increased. In addition, the crystal magnetic anisotropy in each crystal phase 3 is easily averaged, and a soft magnetic powder with low coercive force is obtained. Furthermore, since the magnetic permeability is increased, it is difficult to saturate even under a high current, so that the saturation magnetic flux density of the soft magnetic powder can be easily increased.

[0075] The measurement of crystallite size by X-ray diffraction method is performed by obtaining X-ray diffraction patterns for the soft magnetic powder and the standard sample, estimating the Fe-derived diffraction line width, and then calculating the crystallite size by the Scherrer method. The X-ray diffraction pattern obtained for the standard sample is used to estimate the diffraction line width derived from the device. The crystallite size calculated from the soft magnetic powder (test sample) can be corrected by this diffraction line width.

[0076] 1.6.Various characteristics The average particle size of the soft magnetic powder according to the embodiment is not particularly limited, but is preferably 1 μm or more and 50 μm or less, more preferably 10 μm or more and 45 μm or less, and even more preferably 20 μm or more and 40 μm or less. By using soft magnetic powder with such an average particle size, the path through which eddy current flows can be shortened, so that a magnetic element can be manufactured that can sufficiently suppress eddy current loss generated in the particles of the soft magnetic powder. In addition, the filling rate of the soft magnetic powder in the compact can be increased, and the magnetic permeability and saturation magnetic flux density of the compacted powder core can be increased.

[0077] Furthermore, when the soft magnetic powder has an average particle size of 10 μm or more, a higher green density can be achieved by mixing it with a soft magnetic powder having an average particle size smaller than that of the soft magnetic powder according to the embodiment, which makes it easier to increase the saturation magnetic flux density and magnetic permeability of the powder magnetic core.

[0078] The average particle size of the soft magnetic powder refers to the particle size D50 at which the cumulative frequency is 50% from the small diameter side in the cumulative particle size distribution on a volume basis of the soft magnetic powder obtained using a laser diffraction particle size distribution measuring device.

[0079] If the average particle size of the soft magnetic powder is below the lower limit, the soft magnetic powder may become too fine, which may reduce the packing property of the soft magnetic powder. This reduces the compaction density of the powder core, which may reduce the magnetic permeability and saturation magnetic flux density of the powder core depending on the composition and mechanical properties of the soft magnetic powder. On the other hand, if the average particle size of the soft magnetic powder is above the upper limit, the eddy current loss generated within the particles may not be sufficiently suppressed depending on the composition and mechanical properties of the soft magnetic powder, which may increase the iron loss of the magnetic element.

[0080] The coercive force of the soft magnetic powder according to the embodiment is not particularly limited, but is preferably less than 2.00 [Oe] (less than 160 [A / m]), more preferably 0.10 [Oe] to 1.67 [Oe] (39.9 [A / m] to 133 [A / m]), and even more preferably 0.10 [Oe] to 1.00 [Oe] (39.9 [A / m] to 79.6 [A / m]). By using soft magnetic powder with such a low coercive force, it is possible to manufacture a magnetic element that can sufficiently suppress hysteresis loss even under high frequency. The coercive force may be lower than the lower limit, but there is a risk of increasing the difficulty of manufacture.

[0081] The coercive force of the soft magnetic powder can be measured, for example, by a vibrating sample magnetometer such as TM-VSM1230-MHHL manufactured by Tamagawa Seisakusho Co., Ltd.

[0082] The soft magnetic powder according to the embodiment preferably has a magnetic permeability of 24.0 or more, and more preferably 25.0 or more, at a measurement frequency of 1 MHz when compacted. Such soft magnetic powder has excellent DC superposition characteristics, high electromagnetic conversion efficiency at high frequencies, and contributes to the realization of a compacted magnetic element. This magnetic permeability is determined by compacting the soft magnetic powder together with an epoxy resin added at a ratio of 2 mass% to the soft magnetic powder at a compaction pressure of 294 MPa (3 t / cm). 2) to form a ring shape with an outer diameter of 14 mm, an inner diameter of 8 mm, and a thickness of 3 mm, and then this ring-shaped compact is wrapped with a conductor with a diameter of 0.6 mm seven times and measured. The magnetic permeability is measured using an impedance analyzer such as Agilent Technologies 4194A. The measurement frequency is 1 MHz.

[0083] The saturation magnetic flux density of the soft magnetic powder according to the embodiment is preferably 1.25 [T] or more, and more preferably 1.30 [T] or more, thereby making it possible to obtain a magnetic element that is not easily saturated even with a high current.

[0084] The saturation magnetic flux density of the soft magnetic powder is measured, for example, by the following method. First, the true specific gravity ρ of the soft magnetic powder is measured using a fully automatic gas displacement density meter, AccuPyc1330, manufactured by Micromeritics. Next, the maximum magnetization Mm of the soft magnetic powder is measured using a vibration sample magnetometer, VSM system, TM-VSM1230-MHHL, manufactured by Tamagawa Seisakusho Co., Ltd. Then, the saturation magnetic flux density Bs is calculated using the following formula. Bs = 4π / 10000 × ρ × Mm

[0085] The soft magnetic powder according to the embodiment is mixed with 2% by mass of an epoxy resin, and the resulting mixture is press-molded at a pressure of 294 MPa to obtain a green compact having a density of 4.99 g / cm. 3 It is preferable that the density is 5.01 g / cm or more. 3 More than 5.20g / cm 3 If the density of the powder compact is within the above range, the occupancy rate of oxides in the powder compact can be sufficiently suppressed, and as a result, the occupancy rate of alloy can be sufficiently secured, thereby making it possible to further increase the magnetic permeability and saturation magnetic flux density of the magnetic element.

[0086] The soft magnetic powder according to the embodiment may be mixed with other soft magnetic powders or non-soft magnetic powders, and the mixed powder may be used for various applications.

[0087] 2. Manufacturing method of soft magnetic powder Next, an example of a method for producing the above-mentioned soft magnetic powder will be described.

[0088] The soft magnetic powder may be a powder produced by any method. Examples of the production method include various atomization methods such as water atomization, gas atomization, and rotating water flow atomization, as well as pulverization. Among these, the atomization method is preferably used. According to the atomization method, it is possible to efficiently produce a high-quality metal powder whose particle shape is closer to a perfect sphere and which has less formation of oxides, etc. Therefore, it is possible to produce a metal powder whose specific surface area is smaller by the atomization method.

[0089] The atomization method is a method for producing metal powder by colliding molten metal with a liquid or gas jetted at high speed to pulverize the molten metal and cool it. In the atomization method, the molten metal is atomized and then spherical during the process of solidification, so that particles closer to perfect spheres can be produced.

[0090] Of these, the water atomization method uses a liquid such as water as a coolant, sprays it in an inverted cone shape that converges to one point, and causes molten metal to flow down toward this convergence point and collide with it, thereby producing metal powder from molten metal.

[0091] In addition, the rotary water jet atomization method is a method for producing metal powder by supplying a cooling liquid along the inner surface of a cooling cylinder and rotating it along the inner surface while spraying a liquid or gas jet onto molten metal and incorporating the scattered molten metal into the cooling liquid.

[0092] Furthermore, the gas atomization method is a method of producing metal powder from molten metal by using a gas as a cooling medium, spraying it in an inverted cone shape that converges to one point, and causing molten metal to flow down toward this convergence point and collide with it.

[0093] Each particle of the metal powder thus obtained is composed of an amorphous structure. By subjecting such metal powder to a crystallization treatment (heat treatment), a part of the amorphous structure is crystallized. As a result, a soft magnetic powder containing the above-mentioned amorphous phase 2 and crystalline phase 3 is obtained.

[0094] The temperature of the crystallization treatment is not particularly limited, but is preferably 520°C to 640°C, more preferably 530°C to 630°C, and even more preferably 540°C to 620°C. The time of the heat treatment is preferably 1 minute to 180 minutes, more preferably 3 minutes to 120 minutes, and even more preferably 5 minutes to 60 minutes, during which the temperature is maintained. By setting the temperature and time of the heat treatment within the above ranges, respectively, a crystal phase 3 having a uniform crystallite size in an appropriate range can be generated.

[0095] If the temperature or time of the heat treatment is below the lower limit, depending on the composition of the soft magnetic powder, crystallization may be insufficient, resulting in a small crystallite size or poor uniformity of the crystallite size. On the other hand, if the temperature or time of the heat treatment is above the upper limit, crystallization may proceed too far, resulting in an excessively large crystallite size or poor uniformity of the crystallite size, depending on the composition of the soft magnetic powder.

[0096] The atmosphere for the crystallization treatment is not particularly limited, but is preferably an inert gas atmosphere such as nitrogen or argon, a reducing gas atmosphere such as hydrogen or ammonia decomposition gas, or a reduced pressure atmosphere thereof, which allows crystallization while suppressing oxidation of the metal, and produces a soft magnetic powder with excellent magnetic properties.

[0097] The oxygen concentration in the atmosphere of the crystallization treatment affects the amount of oxides produced. Therefore, the oxygen concentration in the atmosphere of the crystallization treatment is preferably 1000 ppm or less by volume, more preferably 5 ppm or more and 500 ppm or less, and even more preferably 10 ppm or more and 200 ppm or less. This makes it possible to suppress the production of oxides, and obtain a soft magnetic powder that can be used to produce a high-density green compact.

[0098] The heating rate in the crystallization treatment is preferably 1°C / min or more and 80°C / min or less, more preferably 2°C / min or more and 30°C / min or less, and even more preferably 4°C / min or more and 20°C / min or less. By setting the heating rate within the above range, even when a large amount of metal powder is subjected to the crystallization treatment, the unevenness of the heating rate is suppressed, and the crystallite diameter of the soft magnetic powder can be easily controlled within the above range, and the variation in the crystallite diameter can also be suppressed. If the heating rate is below the lower limit, the efficiency of the crystallization treatment may decrease, and the manufacturing efficiency of the soft magnetic powder may decrease. On the other hand, if the heating rate exceeds the upper limit, when a large amount of metal powder is subjected to the crystallization treatment, the variation in the crystallite diameter of the soft magnetic powder may increase, and the coercive force of the soft magnetic powder may increase.

[0099] The cooling rate in the crystallization treatment is not particularly limited, but is preferably 1°C / min to 100°C / min, more preferably 2°C / min to 30°C / min, and even more preferably 4°C / min to 20°C / min. By setting the cooling rate within the above range, it becomes easier to control the crystallite size of the soft magnetic powder within the above range. In addition, it becomes easier to suppress the variation in the crystallite size.

[0100] The soft magnetic powder according to the present embodiment can be manufactured in the above manner. The manufactured soft magnetic powder may be classified as necessary. Examples of classification methods include dry classification such as sieving classification, inertial classification, and centrifugal classification, and wet classification such as sedimentation classification.

[0101] If necessary, an insulating film may be formed on the surface of each particle of the obtained soft magnetic powder. Examples of materials constituting this insulating film include inorganic materials such as phosphates such as magnesium phosphate, calcium phosphate, zinc phosphate, manganese phosphate, and cadmium phosphate, silicates such as sodium silicate, ceramic materials such as silica, alumina, magnesia, zirconia, and titania, and glass materials such as borosilicate glass and silica glass.

[0102] 3. Powder cores and magnetic components Next, the powder magnetic core and the magnetic element according to the embodiment will be described.

[0103] The magnetic element according to the embodiment can be applied to various magnetic elements having a magnetic core, such as a choke coil, an inductor, a noise filter, a reactor, a transformer, a motor, an actuator, an electromagnetic valve, a generator, etc. Furthermore, the powder magnetic core according to the embodiment can be applied to the magnetic cores included in these magnetic elements.

[0104] Two types of coil components will be described below as representative examples of the magnetic element. 3.1.Toroidal type First, a toroidal type coil component, which is an example of a magnetic element according to the embodiment, will be described.

[0105] FIG. 2 is a plan view that illustrates a schematic diagram of a toroidal-type coil component 10. As shown in FIG. A coil device 10 shown in FIG. 2 has a ring-shaped powder core 11 and a conductive wire 12 wound around this powder core 11.

[0106] The powder magnetic core 11 is obtained by mixing the soft magnetic powder according to the embodiment with a binder, supplying the mixture to a molding die, and pressing and molding it. That is, the powder magnetic core 11 is a compact containing the soft magnetic powder according to the embodiment. Such a powder magnetic core 11 has a high molding density and a high magnetic permeability. Therefore, when a coil component 10 having the powder magnetic core 11 is mounted on an electronic device or the like, the electronic device or the like can be made more compact and have higher performance. The binder may be added as necessary, or may be omitted.

[0107] Furthermore, the coil component 10 as a magnetic element including such a powder magnetic core 11 achieves low loss and small size due to the low coercive force and high magnetic permeability of the powder magnetic core 11.

[0108] Examples of materials constituting the binder used in producing the powder magnetic core 11 include organic materials such as silicone resins, epoxy resins, phenol resins, polyamide resins, polyimide resins, and polyphenylene sulfide resins, and inorganic materials such as phosphates such as magnesium phosphate, calcium phosphate, zinc phosphate, manganese phosphate, and cadmium phosphate, and silicates such as sodium silicate, but thermosetting polyimide or epoxy resins are particularly preferred. These resin materials are easily cured by heating and have excellent heat resistance. This makes it possible to increase the ease of production and heat resistance of the powder magnetic core 11.

[0109] The ratio of binder to soft magnetic powder varies slightly depending on the desired saturation magnetic flux density, mechanical properties, allowable eddy current loss, etc. of the powder core 11 to be produced, but is preferably about 0.5% by mass to 5% by mass, and more preferably about 1% by mass to 3% by mass. This makes it possible to obtain a powder core 11 that has excellent magnetic properties such as saturation magnetic flux density and magnetic permeability while sufficiently binding each particle of the soft magnetic powder. Various additives may be added to the mixture for any purpose as necessary.

[0110] The conductive wire 12 may be made of a highly conductive material, such as a metal material containing Cu, Al, Ag, Au, Ni, etc. An insulating film may be provided on the surface of the conductive wire 12 as necessary.

[0111] The shape of the powder magnetic core 11 is not limited to the ring shape shown in FIG. 2, and may be, for example, a ring shape with a part missing, or a shape with a linear shape in the longitudinal direction.

[0112] Furthermore, the powder magnetic core 11 may contain soft magnetic powder other than the soft magnetic powder according to the embodiment described above or non-magnetic powder, as necessary.

[0113] 3.2.Closed magnetic circuit type Next, a closed magnetic circuit type coil component, which is an example of a magnetic element according to the embodiment, will be described.

[0114] FIG. 3 is a see-through perspective view that typically shows a coil component 20 of a closed magnetic circuit type. The closed magnetic circuit type coil component 20 will be described below, but the following description will focus on the differences from the toroidal type coil component 10, and descriptions of similar points will be omitted.

[0115] 3, the coil component 20 according to this embodiment is formed by embedding a conductor wire 22 formed into a coil shape inside a powder magnetic core 21. That is, the coil component 20 is formed by molding the conductor wire 22 with the powder magnetic core 21. This powder magnetic core 21 has a similar configuration to the powder magnetic core 11 described above.

[0116] A relatively small coil component 20 having this configuration can be easily obtained. Furthermore, by reducing the coercive force and increasing the magnetic permeability of the powder magnetic core 21, a coil component 20 with low loss and small size can be obtained.

[0117] Furthermore, because the conductive wire 22 is embedded inside the powder core 21, a gap is unlikely to occur between the conductive wire 22 and the powder core 21. This makes it possible to suppress vibrations caused by magnetostriction of the powder core 21, and also to suppress the generation of noise associated with this vibration.

[0118] The dust core 21 may contain soft magnetic powder other than the soft magnetic powder according to the embodiment described above or non-magnetic powder, as necessary.

[0119] 4.Electronic equipment Next, an electronic device including the magnetic element according to the embodiment will be described with reference to FIGS.

[0120] Fig. 4 is a perspective view showing a configuration of a mobile personal computer 1100, which is an electronic device including the magnetic element 1000 according to the embodiment. The personal computer 1100 shown in Fig. 4 includes a main body 1104 including a keyboard 1102, and a display unit 1106 including a display unit 100. The display unit 1106 is rotatably supported by the main body 1104 via a hinge structure. Such a personal computer 1100 includes a built-in magnetic element 1000, such as a choke coil or inductor for a switching power supply, or a motor.

[0121] Fig. 5 is a plan view showing a configuration of a smartphone 1200 which is an electronic device including the magnetic element 1000 according to the embodiment. The smartphone 1200 shown in Fig. 5 includes a plurality of operation buttons 1202, an earpiece 1204, and a mouthpiece 1206. In addition, a display unit 100 is disposed between the operation buttons 1202 and the earpiece 1204. Such a smartphone 1200 includes a built-in magnetic element 1000 such as an inductor, a noise filter, or a motor.

[0122] 6 is a perspective view showing a configuration of a digital still camera 1300, which is an electronic device including the magnetic element 1000 according to the embodiment. The digital still camera 1300 photoelectrically converts an optical image of a subject using an imaging element such as a CCD (Charge Coupled Device) to generate an imaging signal.

[0123] 6 includes a display unit 100 provided on the back of a case 1302. The display unit 100 functions as a viewfinder that displays a subject as an electronic image. In addition, a light receiving unit 1304 including an optical lens, a CCD, etc. is provided on the front side of the case 1302, i.e., on the back side in the figure.

[0124] When the photographer checks the subject image displayed on the display unit 100 and presses the shutter button 1306, the image signal of the CCD at that time is transferred to and stored in memory 1308. Such a digital still camera 1300 also has a built-in magnetic element 1000, such as an inductor or a noise filter.

[0125] Examples of electronic devices according to the embodiments include a personal computer 1100 in FIG. 4, a smartphone 1200 in FIG. 5, and a digital still camera 1300 in FIG. 6, as well as, for example, a mobile phone, a tablet terminal, a watch, an inkjet discharge device such as an inkjet printer, a laptop personal computer, a television, a video camera, a video tape recorder, a car navigation device, a pager, an electronic organizer, an electronic dictionary, a calculator, an electronic game device, a word processor, a workstation, a videophone, a security television monitor, an electronic binoculars, a POS terminal, medical equipment such as an electronic thermometer, a blood pressure monitor, a blood glucose meter, an electrocardiogram measuring device, an ultrasonic diagnostic device, and an electronic endoscope, a fish finder, various measuring equipment, instruments for vehicles, aircraft, and ships, mobile object control equipment such as automobile control equipment, aircraft control equipment, railway vehicle control equipment, and ship control equipment, and a flight simulator.

[0126] Such electronic devices include the magnetic element according to the embodiment, and can enjoy the effects of the magnetic element, such as low loss and small size, and can reduce the power consumption and size of the electronic devices.

[0127] 5. Effects of the soft magnetic powder according to the embodiment As described above, the soft magnetic powder according to this embodiment has The composition determined by the solid-state optical emission spectrometer (OES) is the composition formula Fe x Cu a Nb b (Si 1-y (B 1-z Cr z ) y ) 100-x-a-b [a, b, x, y, z are 0.3≦a≦2.0, 2.0≦b≦4.0, 75.5≦x≦79.5, 0.55≦y≦0.91, 0.015≦z≦0.185, .] It is expressed as:

[0128] In addition, the soft magnetic powder according to this embodiment has an amorphous phase 2 composed of an amorphous structure in which Fe is the constituent element with the highest concentration, and a crystalline phase 3 composed of a crystalline structure in which Fe is the constituent element with the highest concentration.

[0129] When the Cr content [atomic %] determined by a solid-state optical emission spectrometer (OES) is defined as X(Cr), and the Cr content [atomic %] and B content [atomic %] of the amorphous phase 2 determined by an energy dispersive X-ray fluorescence spectrometer (EDX) are defined as Y(Cr) and Y(B), respectively, the soft magnetic powder according to this embodiment satisfies the following formulas (1) and (2). X(Cr) <Y(Cr)≦X(Cr)+1.0 (1) 3.0≦Y(B)≦15.0 (2)

[0130] According to this configuration, a soft magnetic powder having excellent oxidation resistance and capable of producing a green compact having high density and magnetic permeability can be obtained. In addition, the amorphous phase 2 can be stabilized, and the coarsening of the crystalline phase 3 during the crystallization process can be suppressed regardless of the heat treatment conditions, resulting in a soft magnetic powder having low coercivity and being easy to produce.

[0131] In addition, the soft magnetic powder according to this embodiment preferably satisfies the following formula (3), where Z(Cr) is the Cr content [atomic %] of the crystal phase 3 determined by an energy dispersive X-ray fluorescence analyzer (EDX). Z(Cr) <X(Cr) (3)

[0132] In the soft magnetic powder according to this embodiment, the B content Y(B) [atomic %] of the amorphous phase 2 determined by an energy dispersive X-ray fluorescence analyzer (EDX) preferably satisfies the following formula (4). 3.0≦Y(B)≦10.0 (4)

[0133] According to such a configuration, the Cr content Z(Cr) of the crystalline phase 3 and the B content Y(B) of the amorphous phase 2 are each optimized, and the amorphous phase 2 can be further stabilized.

[0134] Moreover, it is preferable that Y(Cr) [atomic %], Y(B) [atomic %] and the Cr content Z(Cr) [atomic %] satisfy the following formulae (5) to (7). 1.5≦Y(Cr)≦2.5 (5) 4.0≦Y(B)≦7.0 (6) 0.8≦Z(Cr)≦2.0 (7)

[0135] According to this configuration, the Cr content and B content of the amorphous phase 2, and the Cr content of the crystalline phase 3 are each optimized, and the amorphous phase 2 can be further stabilized.

[0136] The oxygen content of the soft magnetic powder is preferably 1500 ppm or less, which can particularly reduce the generation of oxides that cause a decrease in the density of the green compact.

[0137] Moreover, the powder magnetic core according to the embodiment contains the soft magnetic powder according to the embodiment, whereby a powder magnetic core with low coercivity and high magnetic permeability can be obtained.

[0138] Moreover, the magnetic element according to the embodiment includes the powder magnetic core according to the embodiment, thereby achieving low loss and miniaturization of the magnetic element.

[0139] Moreover, the electronic device according to the embodiment includes the magnetic element according to the embodiment, thereby making it possible to obtain an electronic device that is small in size and consumes less power.

[0140] The soft magnetic powder, the dust core, the magnetic element, and the electronic device of the present invention have been described above based on the preferred embodiments, but the present invention is not limited thereto.

[0141] For example, in the above embodiment, a powder compact such as a powder core has been given as an example of an application of the soft magnetic powder of the present invention, but the application examples are not limited to this and may be, for example, a magnetic fluid, a magnetorheological elastomer composition, a magnetic head, an electromagnetic wave shielding member, or a magnetic device such as a magnetic core for an electric motor or a generator.

[0142] Moreover, the soft magnetic powder, the dust core, the magnetic element, and the electronic device of the present invention may be those in which any component is added to the above-described embodiments.

[0143] Furthermore, the shapes of the dust core and the magnetic element are not limited to those shown in the drawings, and may be any shape. EXAMPLES

[0144] Next, specific examples of the present invention will be described. 6. Manufacturing of green compacts 6.1. Sample No. 1 First, the raw materials were melted in a high-frequency induction furnace and pulverized by a rotating water jet atomization method to obtain metal powder.

[0145] Next, the obtained metal powder was subjected to a crystallization treatment in which it was heated in a nitrogen atmosphere. As a result, a soft magnetic powder was obtained. The heating temperature and the temperature increase rate in the crystallization treatment are as shown in Table 1. The temperature decrease rate after heating was 10°C / min. The heating temperatures shown in Table 1 were determined in advance by searching for the heating temperature at which the coercive force of each soft magnetic powder becomes minimum.

[0146] Next, the soft magnetic powder was classified using an air classifier. Next, the classified soft magnetic powder was subjected to composition analysis using a solid-state optical emission spectrometer (OES). The analysis results are shown in Table 1.

[0147] Next, the particle size distribution of the obtained soft magnetic powder was measured, and the average particle size of the soft magnetic powder was found to be 20 μm from the particle size distribution.

[0148] Next, the obtained soft magnetic powder was mixed with an epoxy resin as a binder to obtain a mixture. The amount of the epoxy resin added was 2 parts by mass per 100 parts by mass of the soft magnetic powder (2% by mass of the soft magnetic powder).

[0149] Next, the mixture was stirred and then dried for a short time to obtain a lump-shaped dried body. The dried body was then sieved through a sieve with an opening of 600 μm, and the dried body was pulverized to obtain a granulated powder. The obtained granulated powder was dried at 50° C. for 1 hour.

[0150] Next, the obtained granulated powder was filled into a mold and molded under the following molding conditions, and the binder was cured under the following curing conditions to obtain a green compact.

[0151] <Molding conditions> Molding method: Press molding Shape of the compact: Ring-shaped Compact dimensions: outer diameter 14mm, inner diameter 8mm, thickness 3mm ·Molding pressure: 3t / cm 2 (294MPa)

[0152] <Binder curing conditions> ·Heating temperature: 150℃ Heating time: 0.5 hours Heating atmosphere: Air

[0153] 6.2. Samples No. 2 to 21 A soft magnetic powder and a green compact were obtained in the same manner as in Sample No. 1, except that the production conditions for the soft magnetic powder were changed as shown in Table 1 or Table 2.

[0154] [Table 1]

[0155] [Table 2]

[0156] In Tables 1 and 2, among the soft magnetic powders of each sample number, those that correspond to the present invention are indicated as "Examples", and those that do not correspond to the present invention are indicated as "Comparative Examples".

[0157] 7. Evaluation of soft magnetic powders and compacts (powder cores) 7.1. Crystallite size of soft magnetic powder The crystallite size of the soft magnetic powder of each of the Examples and Comparative Examples was measured by X-ray diffraction. The measurement results are shown in Tables 3 and 4.

[0158] 7.2.Oxygen content of soft magnetic powder The oxygen content of the soft magnetic powders of each of the examples and comparative examples was measured. The oxygen content was measured using an oxygen / nitrogen / hydrogen analyzer, ONH836, manufactured by LECO Corporation. The measurement results are shown in Tables 3 and 4.

[0159] 7.3. Density of green compact The density of the green compacts produced using the soft magnetic powders of each of the Examples and Comparative Examples was measured. The measured densities of the green compacts were evaluated according to the following evaluation criteria. The measurement results are shown in Tables 3 and 4.

[0160] A: The density of the green compact is 5.01g / cm 3 That's all. B: The density of the green compact is 4.99 g / cm 3 More than 5.01g / cm 3 is less than C: The density of the green compact is 4.99 g / cm 3 is less than

[0161] 7.4. Coercive force of soft magnetic powder The coercive force of the soft magnetic powder of each of the Examples and Comparative Examples was measured. The measured coercive force was then evaluated in accordance with the following evaluation criteria. The evaluation results are shown in Tables 3 and 4.

[0162] A: Coercive force is less than 0.90 Oe B: Coercive force is 0.90 Oe or more and less than 1.33 Oe C: Coercive force is 1.33 Oe or more and less than 1.67 Oe D: Coercive force is 1.67 Oe or more and less than 2.00 Oe E: Coercive force is 2.00 Oe or more and less than 2.33 Oe F: Coercive force is 2.33 Oe or more

[0163] 7.5. Saturation magnetic flux density of soft magnetic powder The saturation magnetic flux density of each of the soft magnetic powders obtained in the respective Examples and Comparative Examples was calculated. The calculation results are shown in Tables 3 and 4.

[0164] 7.6. Magnetic Permeability of Powder Compacts The magnetic permeability was measured for the green compacts produced using the soft magnetic powders obtained in each of the Examples and Comparative Examples. The measurement results are shown in Tables 3 and 4.

[0165] In Tables 3 and 4, among the soft magnetic powders of each sample number, those that correspond to the present invention are indicated as "Examples", and those that do not correspond to the present invention are indicated as "Comparative Examples".

[0166] [Table 3]

[0167] [Table 4]

[0168] As is clear from Tables 3 and 4, the soft magnetic powders of each Example had excellent oxidation resistance and a relatively low oxygen content even though they had a high Fe content. In addition, the green compacts produced using the soft magnetic powders of each Example were found to have high density and magnetic permeability. Furthermore, the soft magnetic powders of each Example had low coercivity regardless of the heating rate.

[0169] From the above results, it was confirmed that the present invention can produce a green compact having high density and magnetic permeability, and can also produce a soft magnetic powder that has low coercive force and is easy to produce.

[0170] In addition, results with the same tendency as above were obtained for soft magnetic powder having the same structure as the above example, except that it was manufactured using water atomization instead of rotary water jet atomization. [Explanation of symbols]

[0171] 1...particle, 2...amorphous phase, 3...crystalline phase, 6...Cu segregation phase, 10...coil component, 11...powder core, 12...conductor, 20...coil component, 21...powder core, 22...conductor, 100...display unit, 1000...magnetic element, 1100...personal computer, 1102...keyboard, 1104...main body, 1106...display unit, 1200...smartphone, 1202...operation button, 1204...earpiece, 1206...mouthpiece, 1300...digital still camera, 1302...case, 1304...light receiving unit, 1306...shutter button, 1308...memory

Claims

1. The composition determined by the solid-state optical emission spectrometer (OES) is the composition formula Fe x Cu a Nb b (Si 1-y (B 1-z Cr z ) y ) 100-x-a-b [a, b, x, y, z are 0.3≦a≦2.0, 2.0≦b≦4.0, 75.5≦x≦79.5, 0.55≦y≦0.91, 0.015≦z≦0.185, Satisfy. ] It is expressed as The alloy has an amorphous phase constituted by an amorphous structure in which Fe is a constituent element having the highest concentration, and a crystalline phase constituted by a crystalline structure in which Fe is a constituent element having the highest concentration, A soft magnetic powder characterized in that the following formulas (1) and (2) are satisfied, where X(Cr) is the Cr content [atomic %] determined by a solid-state optical emission spectroscopy (OES) and Y(Cr) is the Cr content [atomic %] and Y(B) is the B content [atomic %] of the amorphous phase determined by an energy dispersive X-ray fluorescence spectroscopy (EDX). X(Cr)<Y(Cr)≦X(Cr)+1.0 (1) 3.0≦Y(B)≦15.0 (2)

2. When the Cr content [atomic %] of the crystal phase determined by an energy dispersive X-ray fluorescence analyzer (EDX) is Z(Cr), the following formula (3) is satisfied: Z(Cr)<X(Cr) (3) The soft magnetic powder according to claim 1, wherein the B content Y(B) [atomic %] of the amorphous phase determined by an energy dispersive X-ray fluorescence analyzer (EDX) satisfies the following formula (4): 3.0≦Y(B)≦10.0 (4)

3. The soft magnetic powder according to claim 2, wherein the Y(Cr) [atomic %], the Y(B) [atomic %] and the Z(Cr) [atomic %] satisfy the following formulas (5) to (7). 1.5≦Y(Cr)≦2.5 (5) 4.0≦Y(B)≦7.0 (6) 0.8≦Z(Cr)≦2.0 (7)

4. 4. The soft magnetic powder according to claim 1, having an oxygen content of 1500 ppm or less.

5. A dust core comprising the soft magnetic powder according to claim 1 .

6. A magnetic element comprising the powder magnetic core according to claim 5 .

7. An electronic device comprising the magnetic element according to claim 6.

Citation Information

Patent Citations

  • Soft magnetic powder, dust core, magnetic element and electronic device

    JP2019189928A